The Effect of Implementing the Smart Tihamah Application on the Level of Savings Participation and Ease of Payment of Education Fees (SPP) for MA Tihamah Putra Students - Muis, Rizal Rahmawan; Kemal, Selva Nouvalia; Rosantia, Rosantia; Cahyani, Dewi; Ali, Mohammad (CV. Strata Persada Academia, 2025)
This study investigates the impact of implementing the Smart Tihamah mobile application on students’ savings participation and the ease of education fee (SPP) payments at MA Tihamah Putra. In the digital era, mobile financial applications are increasingly used by educational institutions to enhance financial efficiency, transparency, and convenience for students and parents. However, few empirical studies have specifically examined the role of educational mobile apps in improving financial behaviors and administrative efficiency at the secondary education level, particularly within Islamic schools. This research adopts a quantitative explanatory approach using structured questionnaires and school documentation to assess the effects of the application. The study sample comprises 100 students selected via stratified random sampling. Results reveal that the Smart Tihamah app significantly enhances both savings participation (R² = 0.56) and tuition payment convenience (R² = 0.61), with statistically significant t-test and F-test values supporting its effectiveness. The findings underscore the importance of digital innovation in promoting financial inclusion and operational improvement in education, while also identifying key contextual factors—such as digital literacy, user trust, and social support—that influence app adoption and impact. The study provides practical insights and theoretical contributions for the development and implementation of educational mobile financial systems aimed at improving student financial outcomes and institutional efficiency.